SELENIUM AND GLUTATHIONE PEROXIDASE IN DIABETES MELLITUS - PRIYA.K.DHAS; TULLANITHI.K.M; SYLVIA JAYAKUMAR; RITA MARY ARUNA (International Journal of Pharma and Bio Sciences, 2015)
The incidence of type 2 diabetes mellitus is rising with the majority of the cases being expected in China and India. In Diabetes mellitus oxidative stress mostly seems to be due to an increase in production of free radicals or sharp reduction in antioxidant defense. Diabetic patients may require more antioxidants compared to healthy individuals. Selenium is an important constituent of the antioxidant enzyme glutathione peroxidase. Deficiency of selenium may also lead to a decreased activity of this enzyme resulting in production of free radicals. Hence this study is done to compare the role of selenium (Se) in Glutathione peroxidase(GPX) activity among the type 2 diabetic patients with healthy controls. 50 Type 2 diabetic patients aged between 30-60 and 50 healthy age matched controls who attended Sri Jayadeva Cardiology and Diabetology institute were included in this study. Their clinical history was obtained. A fasting blood sample was drawn and the biochemical parameters - blood sugar, lipid profile, thyroid profile, Se and GPX were estimated. Statistical analysis was done by Student’s t test. A significant decrease in Se and GPX was observed in diabetic patients when compared to the healthy subjects. A statistically significant increase in TGL, LDL, AIP and a decrease in HDL was observed among the diabetic patients when compared to the healthy subjects. A normal thyroid status was observed in diabetic patients even at low selenium level. Decreased activity of the antioxidant enzyme, GPX may be due to the low level of selenium. Decrease in selenium along with decrease in GPX, reveals that the antioxidant defense mechanism is impaired in diabetic patients which may lead to further complications. Lower HDL and increased AIP level also suggests that the diabetic patients are at increased cardiovascular risk.